1989
DOI: 10.1002/j.1460-2075.1989.tb03435.x
|View full text |Cite
|
Sign up to set email alerts
|

N-myc transgene promotes B lymphoid proliferation, elicits lymphomas and reveals cross-regulation with c-myc.

Abstract: To assess the impact of constitutive N‐myc expression on lymphocytes, we generated lines of transgenic mice bearing the murine N‐myc oncogene coupled to the immunoglobulin heavy chain enhancer (E mu). As in mice carrying an analogous c‐myc construct, E mu‐N‐myc mice exhibit a limited overgrowth of cycling pre‐B cells and eventually succumb to clonal B lymphoid tumours. The endogenous N‐myc and c‐myc alleles are silent in both E mu‐N‐myc and E mu‐myc lymphomas, suggesting that these genes are subject to auto‐ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 35 publications
3
79
0
Order By: Relevance
“…This provided an important in vivo context within which to compare N-myc and L-myc. Rosenbaum et al (1989), Dildrop et al (1989) and Sheppard et al (1998) thus created Em-N-myc transgenic animals and showed that they too develop clonal lymphoid tumors of pre-B and Bcell origin. In the latter case, the disease resembled human follicular lymphoma and followed a more indolent course which may have been attributable to lower levels of transgene expression and/or strain di erences.…”
Section: E Ects Of Myc Gene Gain-and Loss-of-function In Vivomentioning
confidence: 99%
“…This provided an important in vivo context within which to compare N-myc and L-myc. Rosenbaum et al (1989), Dildrop et al (1989) and Sheppard et al (1998) thus created Em-N-myc transgenic animals and showed that they too develop clonal lymphoid tumors of pre-B and Bcell origin. In the latter case, the disease resembled human follicular lymphoma and followed a more indolent course which may have been attributable to lower levels of transgene expression and/or strain di erences.…”
Section: E Ects Of Myc Gene Gain-and Loss-of-function In Vivomentioning
confidence: 99%
“…Several factors may contribute to the di erences in disease phenotypes observed with the N-myc transgenes, namely, the use of mouse strains expressing di erent H-2 antigens, the positional e ect or local environment of transgene integration, transgene copy number, strength of their promoter elements and transgene expression levels. The presence of a vigorous SV40 promoter resulted in elevated N-myc expression levels and gave rise to highly malignant lymphosarcomas on the hybrid C57BL6/SJL (H-2b/s) background (Rosenbaum et al, 1989). The C57BL6/SJL lines were maintained by matings of transgenic males to C57BL6/ SJL females, providing an equal genetic representation of C57BL6 and SJL reminiscent of the original embryo genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Since the sites of transgene insertion have not been reported in any of these studies, no conclusions can be made related to the in¯uences of local chromosomal environment on transgene expression. The unifying features of the aggressive, high-grade transgenic N-myc lymphomas (Rosenbaum et al, 1989;Dildrop et al, 1989) were the high levels of transgene expression noted in tumors and tumor-derived cell lines, and the ability of the tumor cells to adapt stably to growth in vitro. In marked contrast, our Em-N-myc mice exhibited basal level transgene expression and the cells obtained from tumors failed to proliferate in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations